2021
DOI: 10.1055/s-0041-1727214
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Term Neonatal Intensive Care Unit Admissions and a Potential Role for Centralized Remote Fetal Monitoring

Abstract: Objective Centralized remote fetal monitoring (CRFM) has been proposed as a method to improve the performance of intrapartum fetal heart rate (FHR) monitoring and perinatal outcomes. The purpose of this study is to determine whether CRFM was associated with a reduction in unexpected term neonatal intensive care unit (NICU) admissions. Study Design A pre–post design was used to examine the effectiveness of CRFM which was implemented in stages across five hospitals. The exposure group was all women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recent study using such a model for fi ve hospitals suggested that unanticipated term neonatal intensive care unit (NICU) admissions, cesarean births, and operative vaginal birth rates could be decreased (Martin et al, 2021). With over 19,000 live births in their pre-and postimplementation analysis, they found no signifi cant differences between groups on unexpected admission to the NICU after multivariate regression analysis (Martin et al, 2021). In further analysis of each hospital individually, their highest volume teaching hospital noted a decrease in cesarean births, operative vaginal birth rates, and 5-minute Apgar scores of <7, suggesting that in some settings, remote EFM may be associated with lower cesarean and operative vaginal birth rates (Martin et al, 2021).…”
Section: Available Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study using such a model for fi ve hospitals suggested that unanticipated term neonatal intensive care unit (NICU) admissions, cesarean births, and operative vaginal birth rates could be decreased (Martin et al, 2021). With over 19,000 live births in their pre-and postimplementation analysis, they found no signifi cant differences between groups on unexpected admission to the NICU after multivariate regression analysis (Martin et al, 2021). In further analysis of each hospital individually, their highest volume teaching hospital noted a decrease in cesarean births, operative vaginal birth rates, and 5-minute Apgar scores of <7, suggesting that in some settings, remote EFM may be associated with lower cesarean and operative vaginal birth rates (Martin et al, 2021).…”
Section: Available Knowledgementioning
confidence: 99%
“…Studies on the value of a remote centralized monitoring system are sparse. A recent study using such a model for fi ve hospitals suggested that unanticipated term neonatal intensive care unit (NICU) admissions, cesarean births, and operative vaginal birth rates could be decreased (Martin et al, 2021). With over 19,000 live births in their pre-and postimplementation analysis, they found no signifi cant differences between groups on unexpected admission to the NICU after multivariate regression analysis (Martin et al, 2021).…”
Section: Available Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Fetal monitoring is the primary means of monitoring to assess fetal safety and contributes to reducing the risk of stillbirth by detecting fetal hypoxia as early as possible [2,3]. Previous studies have repeatedly demonstrated the clinical value of fetal monitoring in reducing adverse perinatal outcomes (eg, neonatal cerebral palsy, hypoxic-ischemic encephalopathy, or stillbirth) [4,5].…”
Section: Introductionmentioning
confidence: 99%